2008
DOI: 10.1577/m06-200.1
|View full text |Cite
|
Sign up to set email alerts
|

Gear‐Specific Population Demographics of Channel Catfish in a Large Midwestern River

Abstract: Various gear types have been used to sample populations of channel catfish Ictalurus punctatus in lotic systems. However, these gears produce different population characteristics (i.e., recruitment, growth, and mortality). We compared the population demographics of channel catfish in the Wabash River, Indiana, sampled with baited 25‐ and 32‐mm‐bar mesh hoop nets and three‐phase alternating current (AC) electrofishing. Based on catch per unit effort, the relative abundance of channel catfish sampled with 32‐mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 14 publications
5
33
3
Order By: Relevance
“…Studies that used single baited hoop nets to sample Channel Catfish in lotic systems generally have reported catch rates similar to those observed in this study (i.e., 1.5–2.6 fish/net‐night; Quist and Guy ; Colombo et al. ; Barada and Pegg ). For Minnesota River Flathead Catfish, Stauffer and Koenen () reported mean low‐frequency electrofishing catch rates of 27.4 fish/h, but few were larger than 600 mm.…”
Section: Discussionsupporting
confidence: 79%
“…Studies that used single baited hoop nets to sample Channel Catfish in lotic systems generally have reported catch rates similar to those observed in this study (i.e., 1.5–2.6 fish/net‐night; Quist and Guy ; Colombo et al. ; Barada and Pegg ). For Minnesota River Flathead Catfish, Stauffer and Koenen () reported mean low‐frequency electrofishing catch rates of 27.4 fish/h, but few were larger than 600 mm.…”
Section: Discussionsupporting
confidence: 79%
“…(see reviews by Vokoun et al 1997 and Vokoun and Rabeni 1999); however, capture efficiency and size selectivity of most catfish sampling gears are unknown. Colombo et al (2008) reported that different gear types (e.g., hoop nets and electrofishing) used to collect channel catfish I. punctatus produced conflicting population parameter estimates, identifying the need to determine biases associated with each gear. In a 2006 survey by the Catfish Management Technical Committee of the Southern Division of the American Fisheries Society, 61% of the biologists surveyed indicated a need for information regarding sampling gear bias and gear efficiency (Brown 2007).…”
mentioning
confidence: 99%
“…For instance, annual survival in the Red River, Manitoba was 95% (multi‐state model survival parameter; Siddons, ), 85% in the Ottawa River system (catch curve; Haxton & Punt, ) and 77% in the Powder River system (catch curve; Gerhardt & Hubert, ). Conversely, annual survival estimates from a commercially exploited population of channel catfish in the Wabash River, Indiana ranged from 50% to 72% (catch curve; Colombo, Phelps, Garvey, Heidinger & Stefanavage, ). A combination of factors is likely responsible for the lower survival estimates in this study compared to previously published estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated sampling with standardised gears was relied on to provide information on channel catfish population characteristics. Hoopnets have been shown to be effective for assessing size structure for channel catfish populations in rivers (Buckmeier & Schlechte, ); however, different configurations and gear types can influence population variables (Colombo, Phelps, Garvey, Heidinger & Stefanavage, ). Electric fishing was employed to potentially sample larger channel catfish not susceptible to hoop nets configured in this study; however, length frequency distributions were similar between gears.…”
Section: Discussionmentioning
confidence: 99%